Caracterização das crianças com síndrome de Down concomitante ao hipotireoidismo congênito no estado de Mato Grosso, Região Central do Brasil, 2010–2021 - Camila Moraes Mello; Stela Maris Silvestrin (Residência Pediátrica)
OBJECTIVE: Congenital hypothyroidism is a frequent disease in pediatric endocrinology, with a high prevalence among children with Down syndrome. In Brazil, publications on the coexistence of these two syndromes in children are scarce. The aim of this study was to clinically and laboratory characterize children with Down syndrome concomitant with congenital hypothyroidism. METHODOLOGY: This is a cross-sectional and retrospective study with data from medical records of patients with Down syndrome concomitant with congenital hypothyroidism among live births from January 2010 to December 2021, followed at a neonatal screening service in Mato Grosso, Brazil. RESULTS: 318 children with congenital hypothyroidism were analyzed, 11 of them with Down syndrome (prevalence of 1:28.9 among children with congenital hypothyroidism). The most common clinical finding was jaundice (90.0%), followed by macroglossia (80.0%), hypotonia (66.7%) and livedo reticularis (62.5%). Congenital cardiac anomalies occurred in all children with Down syndrome studied. Interatrial communication and patent ductus arteriosus were the most frequent cardiac anomalies. Serum levels of thyrotropin were between 10 µIU/mL and 20 µIU/mL in 63.6% of the sample and in two patients, these values ??were above 100 µIU/mL. In 81.8% of the children, free thyroxine levels were normal. The absolute majority of children did not show thyroid ultrasonographic alteration. CONCLUSIONS: A high prevalence of Down syndrome was observed among patients with congenital hypothyroidism, with the subclinical form of hypothyroidism being the most common presentation. Jaundice, macroglossia and congenital heart disease were the most relevant clinical findings in this study.